The NE Atlantic region: A reappraisal of crustal structure, tectonostratigraphy and magmatic evolution - An introduction to the NAG-TEC project: - Péron-Pinvidic, G.; Hopper, J.R.; Stoker, M.; Gaina, C.; Funck, T.; Árting, U.E.; Doornenbal, J.C. (Geological Society of London, 2017)
The NE Atlantic region and its continental margins (Fig. 1) hold unique information for understanding many aspects of Earth science, from global geodynamics to palaeoceanography and global environmental change. It also holds some of the world’s most important hydrocarbon reserves from the North Sea, along the Atlantic margins of Ireland, Britain and Norway, and into the Arctic in the Barents Sea. Historically, studies in the NE Atlantic were important for establishing many of the key ideas during the early part of the plate tectonic revolution.